2021
DOI: 10.1080/07853890.2021.1957998
|View full text |Cite
|
Sign up to set email alerts
|

Changes in COVID-19 vaccination receipt and intention to vaccinate by socioeconomic characteristics and geographic area, United States, January 6 – March 29, 2021

Abstract: Introduction Previous studies suggested that almost one-third of U.S. adults did not plan to get a COVID-19 vaccine once it is available to them. The purpose of this study was to examine changes in vaccine intentions and attitudes by sociodemographic characteristics and geographic areas, factors associated with vaccination intent, and reasons for non-vaccination among a nationally representative sample of U.S. adults. Methods Data from six waves of the Household Pulse S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 10 publications
8
56
1
Order By: Relevance
“…Recent data indicate that the proportion of U.S. adults who have received at least 1 dose (as of September/October 2021) ranges from 72% to 82% (CDC reports ages 12 and older) ( Centers for Disease Control and Prevention, 2020 , Hamel et al, 2021 , Survey, 2021 ), with Asian, American Indian/Alaska Native and Latino persons reporting the highest rates, depending on the source. In the scientific literature, recent estimates for adults who have received at least one dose range from 64% for Black to 86% for Asian persons (May 2021) ( Nguyen et al, 2021 ). One study examining adults ages 18–39 (March-May 2021) reported vaccination rates ranging from 25% among Black persons to 39% among those classified as from all other races ( Baack et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that the proportion of U.S. adults who have received at least 1 dose (as of September/October 2021) ranges from 72% to 82% (CDC reports ages 12 and older) ( Centers for Disease Control and Prevention, 2020 , Hamel et al, 2021 , Survey, 2021 ), with Asian, American Indian/Alaska Native and Latino persons reporting the highest rates, depending on the source. In the scientific literature, recent estimates for adults who have received at least one dose range from 64% for Black to 86% for Asian persons (May 2021) ( Nguyen et al, 2021 ). One study examining adults ages 18–39 (March-May 2021) reported vaccination rates ranging from 25% among Black persons to 39% among those classified as from all other races ( Baack et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the re-opening of schools and businesses, and increased social gatherings and travel 4 , amplify the need for increased vaccination coverage. Unfortunately, even as vaccination coverage and intent increased from January to March 2021, disparities existed by age, race/ethnicity, and other sociodemographic factors 5 . To follow-up on these early vaccination disparities, the present study assessed trends and differences in vaccination coverage and intent from April to August 2021, and examined changes in reasons for not getting vaccinated using a large, nationally representative survey.…”
Section: Introductionmentioning
confidence: 99%
“… 2-4 Several vaccines that are highly effective in reducing the incidence of hospitalization and death have been authorized; however, vaccine coverage remains insufficient. 5 , 6 Antiviral therapies that reduce the risk of Covid-19 progression are needed. Since trials have shown the need for initiation of treatment as soon as possible after the onset of symptoms, 7-9 such therapies would ideally be readily available and easily administered by the patients themselves.…”
mentioning
confidence: 99%